ANALISIS PERANAN PT. BPR BUANA AGRIBISNIS SARIBUDOLOK DALAM PENGEMBANGAN USAHA PETANI DI KECAMATAN SILIMAKUTA KABUPATEN SIMALUNGUN - Christ Muhvay Rani; Syahril Hakim Nasution (Ekonomi dan Keuangan, 2013)
The purposes of this research is to analyze the beneficial of Bank Perkreditan Rakyat (BPR) Buana Agribisnis Saribudolok for expanding peasant’s enterprise on subdistrict Silimakuta Regency of Simalungun, by the average income of the peasant. The independent variablesused in this research was the capital credit issued by BPR Buana Agribisnis Saribudolok. The data used in this study obtained from 78 peasants which the clientele of the institution, by simple random sampling.  The analysis method used in this study is Descriptive Analysis by Simple Linear Regression, test of godness of fit and test penyimpangan asumsi klasik on SPSS 16.0 programme. The result shows that capital credit issued by BPR significantly affect the expanding peasant’s enterprise on the increasing average income. Key word : individual capital, credit, average income